The Effect of Attitude and Knowledge on Saving Interest in Islamic Banks among Islamic Economics Students of Airlangga University with Religiosity as a Moderating Variable - Lina Nugraha Rani; Muhammad Alvin Ramadhan (Airlangga Journal of Innovation Management, 2026)
This study aims to analyze the factors that influence the interest of Islamic Economics students at Airlangga University in saving at Islamic Banks. The sample used in this study were 92 respondents. This research uses quantitative methods, the analysis technique used is SEM PLS (Structural Equation Models Partial Least Square) with religiosity as a moderating variable. The results showed that religiosity statistically had no significant effect on students' interest in saving through Islamic banks. While attitude and knowledge have a positive and significant effect on students' interest in saving through Islamic banks. Religiosity cannot moderate attitude and knowledge on interest in saving through Islamic banks. These results indicate that the level of religiosity of students cannot determine the desire of students to save through Islamic Bank. Based on these results, this study can have implications for Islamic financial institutions, and other parties in order to collaborate in promoting and educating the public about investing and saving through social media and advertisements. This is important because the understanding of the general public, especially the younger generation, is still limited in investing or saving in the Islamic Bank.